SUFFERING IN CHRIS GARDNER’S AUTOBIOGRAPHY THE PURSUIT OF HAPPYNESS - Elsa Violita; Devi Pratiwy (JOURNAL OF LANGUAGE, 2019)
This research is to reveal The Protagonist’s Suffering Depicted in Chris Gardner’s Autobiography: The Pursuit of Happyness. The research adopts qualitative research method in its analysis. The main theory used in this research stated that suffering can be defined as a state of severe distress associated with events that threaten the intactness of the person. It can occur in relation to any aspect of the person in the realm of his social role, his group identification, his relation with self or body, or in relation to family or relation with a personal or transcendental source of meaning. The experience of being hurted since he was child makes the protagonist grows with wisdom and maturity. He considers that all the suffering he faces is a part of life that he must pass. It is also found that the protagonist passes his suffering patiently and thinking positively without blaming other people or the situation which make him suffer.